Binge-type eating disorders and ultra-processed food addiction: phenomenology, pathophysiology and treatment implications - Ifland, Joan; Brewerton, Timothy D. (Frontiers in Psychiatry, 2025)
Background and objectiveDespite their clinical differences, loss of control binge eating (LCBE) is a core feature of all binge-type eating disorders (EDs), including binge eating disorder (BED), bulimia nervosa (BN), and anorexia nervosa binge purge type (AN-BP). The emerging concept of food addiction (FA), or ultra-processed food addiction (UPFA), is also characterized by LCBE. However, LCBE treatment has rejected addiction recovery approaches, especially abstinence or reduced harm through reduced use, to the detriment of patients. Treatment could be more successful if barriers to addiction recovery protocols such as reduced harm and abstinence were addressed.Hypothesis and theoryThe phenomenology and clinical features of binge-type EDs and UPFA overlap considerably, yet they also have distinct clinical features and treatment approaches. Among their commonalities, these conditions share pathophysiological mechanisms. Specifically, available evidence demonstrates that LCBE, regardless of diagnosis, is characterized by alterations in neurobiological systems mediating reward sensitivity, stress reactivity, and cognitive function that are similar to the disturbances found in Ultra-Processed Food Addiction (UPFA), Alcohol Use Disorder (AUD) and other substance use disorders (SUDs). Ultra-processed foods (UPFs) used by patients with LCBE have clearly been shown to have powerful addictive properties. However, the key substance use disorder (SUD) recovery protocols of harm reduction or abstinence from addictive substances are not commonly employed in the treatment of binge-type EDs. The objectives of this paper are to organize evidence that the LCBE characteristic of binge-type EDs and UPFA overlap in many cases and to consider the impact of these findings on treatment protocols, specifically the application of harm reduction and/or abstinence from psychoactive UPFs. This hypothesis can be tested in clinical trials of individuals with LCBE.ResultsNeurobiological studies of individuals with LCBE consistently show signs of addictive alterations, especially hyperactive reward centers, stress reactivity, and cognitive impairment, as well as maladaptive use of UPFs. This is very similar to the results of addictive use of alcohol for which abstinence and harm reduction are demonstratively helpful. However, this approach has not been used in the eating disorders field which may be to the detriment of patients with LCBE.DiscussionThese findings suggest that treatment outcomes for binge-type EDs characterized by LCBE might improve if harm reduction and/or abstinence protocols for recovery from UPFA were applied. A level of support high enough for a severe addiction could improve treatment outcomes for these often recurrent and treatment refractory disorders. Possible rationales for current treatment exclusion or marked reduction of UPF abstinence protocols are offered.